Kerogen Pyrolysis: The Constructions and Pyrolysis of 3D Kerogen Macromolecular Models: Experiments and Simulations (Global Challenges 5/2019). Issue 5 (3rd May 2019) - Wang, XiaoHe; Huang, XianFu; Lin, Kui; Zhao, Ya‐Pu
Abstract : Kerogen in deep stratum are cracked to produce shale oil and gas. In article number1900006 by Ya‐Pu Zhao and co‐workers, 2D molecular models of kerogen are obtained by a series of physical and chemical experiments. This study proposes the mechanisms of typical reactions of kerogen pyrolysis, which may help to understand the formation of shale oil and gas.